CULTURAL PRODUCTION AND EPHEMERAL ART: FEMINICIDE AND THE GEOGRAPHY OF MEMORY IN CIUDAD JUÁREZ, 1998-2008 - Driver, Alice Laurel (2011)
This dissertation examines representations of feminicide victims in documentary film, novels, non-fiction, art, and graffiti and argues that these images express anxiety about they way women traverse and inhabit the geography of Ciudad Juárez, often giving precedence to the idea of the public female body as hypersexualized. In order to reclaim memory of the victims some cultural producers focus on the testimonial form in which victims’ families and other activists share their stories or construct informal memorials in the city; these remembrances later appear in works of non-fiction, film, and art, as markers of the process of creating and preserving memory. My dissertation analyzes such works as the documentary Señorita extraviada (2001) by Lourdes Portillo, the non-fiction work Huesos en el desierto (2002) by Sergio González Rodríguez, and the novel 2666 (2004) by Roberto Bolaño, among other cultural expressions, to show how feminicide victims and their families have been marked by and have challenged a pervasive public discourse about female sexuality